Essential University Physics: Volume 1 (4th Edition)

Published by Pearson
ISBN 10: 0-134-98855-8
ISBN 13: 978-0-13498-855-9

Chapter 13 - Exercises and Problems - Page 246: 44


The proof is below.

Work Step by Step

Equation 13.3 is: $m\frac{d^2x}{dt^2}=-kx$ If the given equation is a solution to equation 13.3, it will result in a true statement when plugged into equation 13.3. Thus, we find: $m\frac{d^2x}{dt^2}=-kx$ $m\frac{d^2(Asin\omega t)}{dt^2}=-kAsin\omega t$ $-mA\omega^2=-kA$ We know that $\omega^2 = \frac{k}{m}$, so we find: $-mA \frac{k}{m}=-kA$ $-kA=-kA$ This is true, so we see that the given equation is a solution to equation 13.3.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.